Classifying pictorial interpretation theories - Juan Pablo Aguilar Martínez (Prometeica)
Analytic philosophy traditionally uses two classification criteria to distinguish theories of pictorial interpretation: mimetic or illusionistic, and natural or non-natural. In this paper, I propose an alternative and previously unconsidered criterion to classify these theories, based on the type of theory-ladenness argument they employ, whether it is strong or weak. I defend that this third criterion offers four advantages over traditional approaches: (i) it allows a clear distinction between theories of image interpretation that could not be differentiated using previous criteria; (ii) it enables the association of theories previously considered distinct; (iii) it facilitates the recognition of the epistemic and ontological commitments of the theories, allowing a more precise appreciation of their strengths and weaknesses; and (iv) it provides a basis for using literature on the architecture of the mind to argue for or against contemporary theories of image interpretation.